Broadly Reactive IgG Responses to Heterologous H5 Prime-Boost Influenza Vaccination Are Shaped by Antigenic Relatedness to Priming Strains - Wang, Jiong; Li, Dongmei; Perry, Sheldon; Hilchey, Shannon P.; Wiltse, Alexander; Treanor, John J.; Sangster, Mark Y.; Zand, Martin S. (mBio, 2021)
The antigenic shift and draft of hemagglutinin (HA) in influenza viruses is accepted as one of the major reasons for immune evasion. The analysis of B cell immune responses to influenza infection and vaccination is complicated by the impact of exposure history and antibody cross-reactions between antigenically similar influenza strains. Prime-boost vaccinations of humans with different H5 strains have generated broadly protective antibody levels. However, the effect of an individual’s H5 exposure history on antibody responses to subsequent H5 vaccination is poorly understood. To investigate this, we analyzed the IgG responses to H5 influenza A/Indonesia/5/2005 (Ind05) virus vaccination in three cohorts: (i) a doubly primed group that had received two H5 virus vaccinations, namely, against influenza A/Vietnam/203/2004 (Vie04) virus 5 years prior and A/Hong Kong/156/1997 (HK97) 11 years prior to the Ind05 vaccination; (ii) a singly primed group that had received a vaccination against Vie04 virus 5 years prior to the Ind05 vaccination; and (iii) an H5-naive group that received two doses of the Ind05 vaccine 28 days apart. Hemagglutinin (HA)-reactive IgG levels were estimated by a multiplex assay against an HA panel that included 21 H5 strains and 9 other strains representing the H1, H3, H7, and H9 subtypes. Relative HA antibody landscapes were generated to quantitatively analyze the magnitude and breadth of antibody binding after vaccination. We found that short-interval priming and boosting with the Ind05 vaccine in the naive group generated a low anti-H5 response. Both primed groups generated robust antibody responses reactive to a broad range of H5 strains after receiving a booster injection of Ind05 vaccine; IgG antibody levels persisted longer in subjects who had been doubly primed years ago. Notably, the IgG responses were strongest against the first priming H5 strain, which reflects influenza virus immune imprinting. Finally, the broad anti-H5 IgG response was stronger against strains having a small antigenic distance from the initial priming strain. IMPORTANCE The antigenic shift and draft of hemagglutinin (HA) in influenza viruses is accepted as one of the major reasons for immune evasion. The analysis of B cell immune responses to influenza infection and vaccination is complicated by the impact of exposure history and antibody cross-reactions between antigenically similar influenza strains. To assist in such analyses, the influenza “antibody landscape” method has been used to analyze and visualize the relationship of antibody-mediated immunity to antigenic distances between influenza strains. In this study, we describe a “relative antibody landscape” method that calculates the antigenic distance between the vaccine influenza strain and other H5 strains and uses this relative antigenic distance to plot the anti-H5 IgG levels postvaccination. This new method quantitatively estimates and visualizes the correlation between the humoral response to a particular influenza strain and the antigenic distance from other strains. Our findings demonstrate the effect of a subject’s H5 exposure history on H5 vaccine responses quantified by the relative antibody landscape method.